A compilation of 13 patients with metastatic colorectal cancer and concomitant BRAF and RAS family mutations - Srivastav, Jigisha; Lehman, Morgan E.; Evans, Joni K.; Paluri, Ravi; Rocha Lima, Caio Max Sao Pedro (Frontiers in Oncology, 2025)
IntroductionMetastatic colorectal cancer (mCRC) exhibits significant heterogeneity in molecular profiles, influencing treatment response and patient outcomes. Mutations in v-raf murine sarcoma viral oncogene homolog B1 (BRAF) and rat sarcoma (RAS) family genes are commonly observed in mCRC. Though originally thought to be mutually exclusive, recent data have shown that patients may present with concomitant RAS and BRAF mutations, posing unique challenges and implications for clinical management.MethodsBelow we present a retrospective study on 13 patients with concomitant BRAF and RAS (KRAS, NRAS) mutations in mCRC and describe their clinical features and treatment outcomes. We reviewed over 750 samples from a database of CRC patients from Guardant360 and FoundationOne kept by the Wake Forest Baptist Health Comprehensive Cancer Center. The study population included patients greater than the age of 18 who were diagnosed with mCRC harboring both BRAF and RAS mutations, as identified by next generation sequencing.ResultsThirteen mCRC patients, 61.5% male, with a median age of diagnosis of 64.4 years had concomitant BRAF and RAS mutation. 61.5% of patients had right-sided primary disease. 61.5% patients had mutations in codon 12 of KRAS, 15.4% had BRAF G466V, and 15.4% had BRAF V600E mutations. 69.2% patients had liver metastasis, 23.1% had peritoneal metastases and 7.7% suffered metastasis to supraclavicular, retroperitoneal, and mesenteric lymph nodes. Median time from diagnosis of stage IV disease to progression was 25.3 months and median overall survival was 4.9 years.DiscussionThis study adds more insight to the limited existing data regarding rare mCRC cases with concomitant BRAF and RAS family mutations and exposes the need for future research on larger populations of this rare subset of patients.